KUALITAS AIR DAN BEBAN PENCEMARAN PESTISIDA DI SUNGAI BABON KOTA SEMARANG - Rossi Prabowo; Renan Subantoro (Universitas Wahid Hasyim, 2012)
River is an important component of the environment can not be separated from agricultural fields and plantations. Rivers play an important role in irrigation of agricultural crops and plantation society. Baboons current river conditions are thought to have experienced a decline in water quality due to various human activities such as residential, agricultural and industrial. Water quality degradation caused by agriculture and plantations because in order to increase agricultural production and farming, both quantitative and qualitative, have supported the use of pesticides. In its implementation, the use of these pesticides often do not follow the rules, which tend to be in high quantity in order to get quick results in halting the growth of pests and diseases. Pesticides used on farm fields, most or even all will fall into the water and polluting the waters. This study aims to analyze the water quality of the river baboons by river water quality standards according to Government Regulation No. 82 of 2001, as well as analyzing the pollution load entering the river Pesticides baboons derived from agricultural activities. The results showed BOD and COD at some point has exceeded the quality standard required. The index value of the upstream to downstream pollution tends to increase, exceeding the quality standards specified in the criteria unyuk river water quality standard Class II. River baboons have contained residues of endosulfan insecticide in concentrations ranging from 0.6 to 3.0 ug / L.